English for science - Trần, Xuân Điệp (Đại học Sư phạm Hà Nội, 2006)
The purpose of this course, as its title indicates, is provide students of scientific subjects (including medicine, engineering and agriculture) with core of scientific English. This basic language is made up of sentence patterns, structural (functional) words and non-structural vocabulary of each discipline is superimposed. The course has been designed on the belief that once this basic language has been mastered - together with the principal world-building devices (prefixes and suffixes) also presented in this book - the acquisition of these special vocabularies presents very little difficulty, since they are mainly international words and therefore very similar to those already used in Vietnamese, the learners' mother tongue.